LncRNA NRIR inhibits osteogenesis by promoting macrophage M1 polarization through RSAD2/NF-κB axis in peri-implantitis - Zhao, Renshengjie; Wang, Lan; Zhou, Yang; Xiao, Keming; Liu, Qiqi; Yu, Ke (Frontiers in Immunology, 2025)
IntroductionPeri-implantitis is an inflammatory condition affecting the hard and soft tissues surrounding osseointegrated implants, characterized by progressive alveolar bone destruction. The long non-coding RNA Negative Regulator of Interferon Response (lncRNA NRIR) is widely recognized as a biomarker for certain autoimmune diseases and participates in their pathogenesis. However, our previous studies revealed significant upregulation of NRIR in peri-implantitis, suggesting its potential role in peri-implantitis. In peri-implantitis lesions, there is often a substantial infiltration of M1 macrophages. Thus, this study investigated the regulatory role and underlying mechanisms of NRIR in macrophage polarization during peri-implantitis.MethodsTranscriptome sequencing analysis revealed radical S-adenosyl methionine domain containing 2 (RSAD2) as an NRIR-interacting mRNA in macrophages. Using siRNA gene knockdown technology, we suppressed NRIR and RSAD2 expression in M1 macrophages derived from THP-1 cells. Subsequently, we employed RT-qPCR, Western blot, flow cytometry, and immunofluorescence staining to assess the levels of inflammatory cytokines and M1 macrophage-associated markers, aiming to elucidate the involvement of NRIR/RSAD2/NF-κB axis in macrophage polarization. Supernatants from NRIR-knockdown macrophages were collected to prepare the culture medium for bone marrow mesenchymal stem cells (BMSCs). The expression of osteogenic-related factors in BMSCs was evaluated through RT-qPCR, Western blot, Alkaline phosphatase (ALP) activity, and alizarin red S (ARS) staining. Furthermore, a rat peri-implantitis model was established, and the degree of peri-implant tissue inflammation and bone loss was assessed using micro-CT scanning and immunohistochemistry after treatment with various macrophage supernatants.ResultsNRIR knockdown reduced RSAD2 expression and suppressed activation of the NF-κB pathway, consequently decreasing inflammatory cytokines and M1 macrophage-associated cytokine expression in THP-1 macrophages. Functionally, NRIR knockdown in macrophages promoted osteogenic differentiation of BMSCs. In vivo experiments showed that supernatants derived from NRIR-knockdown macrophages resulted in reduced inflammatory infiltration, diminished bone resorption, and increased expression of osteogenesis-related factors.DiscussionThis study demonstrates that NRIR functions as a pro-inflammatory modulator in peri-implantitis by activating M1 macrophages through the RSAD2/NF-κB axis, providing novel insights into peri-implantitis pathogenesis that may inform future preventive and therapeutic strategies.